Analisis Sensori Manisan Jahe Merah (Zingiber Officinale Var. Rubrum) - Ruri Wijayanti; Arsan Arsan (LPPM Universitas Dharma Andalas, 2023)
The purpose of this study was to determine the most preferred concentration of palm sugar and granulated sugar based on organoleptic tests. A food assessment method that uses the five senses is an organoleptic assessment and is generally called a sensory test. The results showed that the most preferred candied red ginger with the addition of palm sugar and granulated sugar was treatment E (added 40% palm sugar and 60% granulated sugar) with a preference value for taste 3.40 (like), aroma 3.72 (like ) and texture 3.56 (like) on a rating scale of 5.